PISA-LIKE MATHEMATICS PROBLEMS: USING TAEKWONDO CONTEXT OF ASIAN GAMES - Dewi Rawani; Ratu Ilma Indra Putri; Hapizah Hapizah (Journal on Mathematics Education, 2019)
This research aims to produce a valid, practical, and having potential effects PISA-like mathematics problems using taekwondo context in Asian Games. The subjects were MIA 3 student of SMA 10 Palembang. This study was design research of development study in which had two stages: the preliminary and formative evaluation. The formative evaluation includes self-evaluation, one-to-one and expert review, small group, and field test. The context is used to have the students estimate maximum numbers of exercising athletes in a hall with a specific size. The result of the analysis shows that the problems which were reviewed by three expert reviews are valid qualitatively based on the PISA framework; it is also practical and easy to understand the problem. Based on the analysis of students’ answer, the developed problems display potential effects on student’s diverse basic mathematical abilities on the various process of answering the problems. The basic mathematics abilities emerging among which are reasoning and argument ability. It appears that students can develop and solve the problem by modeling using their assumptions. Also, the other ability is designing strategies to solve problems in which students use various procedures in solving problems leading the conclusion.